Characterization of collagen and fatty acid composition of “Carne Mirandesa-PDO” veal - Galvão, Lurdes (2011)
The objective of this study was to evaluate chemical parameters related to meat quality, contributing to a better characterization of “Carne Mirandesa-PDO” veal. This study was made in three farms, from the Northeast region of Portugal (PG, FA1 and FA2), where calves were raised permanently indoors, nurse from their dams overnight, and fed with hay and concentrate made with local ingredients and soybean meal. Twenty five calves were slaughtered at 7 months old. Twenty four hours after slaughter, samples were collected from four different muscles: longissimus dorsi (LD), semimembranosus (SM), gluteus biceps femoris (GB) and triceps brachii caput longum (TBL), vacuum packaged and freeze-dried. Determinations of crude protein (CP), ether extract (EE), collagen and fatty acid were made. Collagen, CP and EE were significantly (p<0.001) affected by muscle type. Fatty acid composition was mostly affected by farm and by muscle type. The SM muscle was poor in saturated fatty acids (14:0, 15:0, 16:0, 17:0 and 18:0) and richer in polyunsaturated fatty acids than the other muscles. The ratio between n-3 and n-6 PUFA observed in this study are close to the usually found for pasture fed animals indicating the healthy value of “Carne-Mirandesa PDO” veal.